Ultra-fast Liquid Chromatographic Determination of Potential Genotoxic Impurities in Dasatinib Drug Substance at Trace Level - N. Balaji; Sayeeda Sultana (Challenges and Advances in Pharmaceutical Research Vol. 10, 2022)
A simple, cost-effective, and mass compatible ultra-high rapid performance liquid chromatographic (Agilent - Infinity LC 1290) approach for identifying possible genotoxic contaminants in dasatinib medication has been developed and validated. The mobile phase is trifluoroacetic acid, acetonitrile, and water, the column used is zorbax RRHD eclipse plus C18 with length of 50 mm, internal diameter of 2.1 mm and particle size of 1.8 microns. The limit of detection and limit of quantification of the potential genotoxic impurities are less than 0.1 \(μ\)g/ml, and 0.3 \(μ\)g/ml with respect to dasatinib test concentration of 1000 \(μ\)g/ml. This approach has been validated in accordance with ICH recommendations Q2 (R1).